METAPHOR AND METONYMY (Modern education and development, 2025)
The article “Metaphor and Metonymy ” explores two fundamental tropes of language: metaphor and metonymy.Metaphor is defined as a tool for understanding one concept in terms of another based on similarity, while metonymy functions through association or contiguity. The article also references Roman Jakobson’s theoretical framework, highlighting the complementary roles of metaphor and metonymy in literature and thought. This concise overview provides valuable insight for linguists, literary scholars, and language learners interested in figurative language and conceptual mapping.